AWARENESS, KNOWLEDGE AND ATTITUDE OF COMPUTER-AIDED DESIGNING AND COMPUTER-AIDED MANUFACTURING AMONG DENTAL SURGEONS IN LAHORE, PAKISTAN - Khadija Imran; Aaqil Malik; Usman Yousaf; Hamna Hoor; Muhammad Afzal; Gulrez Amin (Pakistan Oral & Dental Journal, 2024)
The application, knowledge, and attitude dentists towards CAD/CAM technology in Pakistan showed very few publications. Objective: The purpose of this study was to evaluate the awareness, knowledge, and attitude towards CAD and CAM among postgraduate dental students and practitioners in Pakistan. Methodology: A cross-sectional questionnaire-based survey was conducted at various institutions including University College of Dentistry UOL, Fatima Memorial Hospital, private clinics throughout Lahore that focused on postgraduate students, private dental practitioners, and teaching faculty. Data was collected from September 2022 to November 2022. SPSS version 20.0 software was used to analyze the data collected through a Chi-square test to determine if there were any significant correlations between questionnaire items and practitioner type with a p-value significance level set at 0.05. Results: The study had 220 participants. 118 (53.6%) house surgeons, 39 (17.7%) postgraduates, 26 (11.8%) private practitioners and 37 (16.8%) were teaching faculty. About 70% of the participants believed that CAD/CAM technology could be applied to implant restorations while 60 (27.3%) knew about its use for digital impressions; 40 (18.2%) acknowledged its superior precision as compared to conventional methods. In addition to this, the study found that 122 (55 5 %) participants deemed less chair-side time required by CAD/CAM advantageous in clinical scenarios. Conclusion: This study showed that awareness about CAD/CAM does exist among dentists; however, they have very scarce knowledge about its applications to clinical settings and an urgent need at the undergraduate and post graduate level is needed.